MANAJEMEN KEUANGAN SEKOLAH DALAM PEMENUHAN SARANA PRASARANA PENDIDIKAN (STUDI KASUS DI SD MUHAMMADIYAH 1 KRIAN, SIDOARJO) - Rita Pusvitasari; Mukhamad Sukur (JURNAL AL-TANZIM, 2020)
This study aims to analyze and understand school financial management in fulfilling educational infrastructure facilities at SD Muhammadiyah 1 Krian, Sidoarjo, East Java. This research uses a qualitative approach with case study. Informants in this study consisted of leader, secretary, and treasurer. Data collection techniques are carried out using interviews, participant observation, and documentation. The data analysis technique uses data reduction, data display, and conclusion drawing / verification. Checking the validity of the data is done through; credibility, transferability, dependability, and confirmability. The results showed that; school financial management in fulfilling educational infrastructure facilities at SD Muhammadiyah 1 Krian was carried out through; school budget planning, school budget absorption, accounting for school finances, school financial accountability. This research has implications for the importance of financial management in the fulfillment of educational facilities and infrastructures, through involving stakeholders, both internal and external, to evaluate, analyze, supervise and meet various school needs.